The safety of colorectal cancer surgery during the COVID-19: a systematic review and meta-analysis - Wang, Qiuxiang; Wu, Ruike; Wang, Juan; Li, Yilin; Xiong, Qin; Xie, Fengjiao; Feng, Peimin (Frontiers in Oncology, 2023)
Abstract: Background: The ongoing COVID-19 pandemic has placed unprecedented pressure on the healthcare systems. This study evaluated the safety of colorectal cancer (CRC) surgery during the COVID-19 pandemic. Methods: A systematic review and meta-analysis were performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses （PRISMA） guidelines (PROSPERO ID: CRD 42022327968). Relevant articles were systematically searched in the PubMed, Embase, Web of Science, and Cochrane databases. The postoperative complications, anastomotic leakage, postoperative mortality, 30-day readmission, tumor stage, total hospitalization, postoperative hospitalization, preoperative waiting, operation time, and hospitalization in the intensive care unit (ICU) were compared between the pre-pandemic and during the COVID-19 pandemic periods. Results: Among the identified 561 articles, 12 met the inclusion criteria. The data indicated that preoperative waiting time related to CRC surgery was higher during the COVID-19 pandemic (MD,0.89; 95% CI:0.43 to 1.35, P＝0.0001). A similar trend was observed for the total operative time (MD,24.05; 95%CI, 13.08 to 35.01; P ＜0.0001), and during the T4 of tumor stage (OR, 1.63; 95%CI, 1.16 to 2.29; P=0.005). However, there was no difference in the postoperative complications, postoperative 90-day mortality,anastomotic leakage, and 30-d readmission times between pre-COVID-19 pandemic and during the COVID-19 pandemic periods. Furthermore, there was no difference in the total hospitalization time, postoperative hospitalization time, and hospitalization time in ICU related to CRC surgery before and during the COVID-19 pandemic. Conclusion: The COVID-19 pandemic did not affect the safety of CRC surgeryThe operation of CRC during the COVID-19 pandemic did not increase postoperative complications, postoperative 90-day mortality,anastomotic leakage, 30-day readmission, the total hospitalization time, postoperative hospitalization time and postoperative ICU hospitalization time. However, the operation of CRC during COVID-19 pandemic increased T4 of tumor stage during the COVID-19 pandemic. Additionally, the preoperative waiting and operation times were longer during the COVID-19 pandemic.